Prevalence of Neisseria gonorrhea in Fertile and Infertile Women in Tehran - B Hossein Rashidi; L Chamani Tabriz; F Haghollahi; M Jeddi-Tehrani; F Ramezanzadeh; A Rahimi Foroushani; M Shariat; MM Akhondi; F Daneshjoo (JRI, 2009)
Introduction: Gonococcal infection is one of the most common bacterial infections, especially in developing countries, but limited information is available about its prevalence in fertile and infertile women in Iran. Therefore, this study was set up to determine the prevalence of the disease in the aforementioned populations in Tehran.Materials and Methods: In this cross-sectional study, 209 infertile women as the cases, and 170 pregnant women in the third trimester of pregnancy as the controls, were evaluated for signs and symptoms of gonococcal infection through interviews. A first-catch urine sample (15ml) was collected from each subject for the detection of Neisseria gonorrhea by PCR method. The data from questionnaires and molecular evaluation were statistically analyzed.Results: PCR testing on urine specimens of fertile and infertile women showed no Neisseria gonorrhea infections.Conclusion: Absence of Neisseria gonorrhea infection in infertile and pregnant women in Tehran could signify the success of health initiatives and preventive measures taken in Iran.
Keywords: Infertility, Neisseria gonorrhea, Polymerase chain reaction, Pregnancy